Ideal Cardiovascular Health and Risk of Frailty in Older Adults. (May 2016) - Graciani, Auxiliadora; García-Esquinas, Esther; López-García, Esther; Banegas, José R.; Rodríguez-Artalejo, Fernando
Abstract : Background—: The major cardiovascular risk factors and existing cardiovascular disease have been linked to increased risk of the frailty syndrome. However, the association between ideal cardiovascular health and the risk of frailty in older adults is uncertain. Methods and Results—: Prospective cohort study of 1745 individuals (≥60 years and free of cardiovascular disease) recruited during 2008 to 2010. Cardiovascular health was defined as having 7 ideal metrics: never smoking, physically active, healthy diet, body mass index <25 kg/m 2, untreated serum cholesterol <200 mg/dL, untreated blood pressure <140/90 mm Hg, and untreated fasting serum glucose <100 mg/dL. Participants were followed-up through 2012 to assess incident frailty, defined as ≥3 of the 5 Fried criteria. Statistical analyses were performed with Cox regression and adjusted for main confounders. During a mean follow-up of 3.5 years, 117 cases of incident frailty were identified. Compared with meeting 0 to 1 ideal metrics, the hazard ratio (95% confidence interval) of frailty was 0.51 (0.30–0.84) for 2 metrics and 0.630 (0.39–0.99) for ≥3 metrics. Results were similar after excluding incident cases of cardiovascular disease. The number of ideal metrics showed a tendency to a reduced risk of all frailty criteria. The cardiovascular metrics associated with the greatest reduction of frailty risk were being physically active and ideal body mass index. Conclusions—: Reaching old age in ideal cardiovascular health is associated with a reduced risk of frailty. This highlights the importance of a life-course approach for frailty prevention. Abstract : Supplemental Digital Content is available in the text.